What are the Key Determinants of Human Resource Management Effectiveness in Enhancing Organizational Financial Performance? - Rosyafah, Siti; Pudjowati, Juliani (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aims to investigate the key determinants of Human Resource Management (HRM) effectiveness and their implications for organizational financial performance. A structured literature review methodology was employed to synthesize findings from various academic databases and sources, including Google Scholar, JSTOR, ScienceDirect, and business-focused databases like Business Source Premier. Keywords such as "human resource management," "organizational financial performance," "talent management," "training and development," and "performance management" were used to refine the search. The review focused on theoretical frameworks such as the Resource-Based View, Human Capital Theory, Strategic HRM Model, Social Exchange Theory, and Contingency Theory, as well as empirical studies examining the relationship between HRM practices and financial outcomes. The findings suggest that strategic alignment between HRM and organizational strategy is crucial for enhancing financial performance, along with effective talent management, training and development initiatives, and performance management systems. Moreover, organizational culture and the impact of technology were identified as important moderating and mediating factors influencing the effectiveness of HRM practices. The study underscores the need for HRM practitioners to align HRM practices with organizational strategy, invest in talent development, and leverage technology to drive organizational success. The synthesis of research findings provides valuable insights for both scholars and practitioners seeking to understand and enhance the effectiveness of HRM in achieving organizational financial performance.